A cog in the capitalist wheel: co-opting agroecology in South India - Ramdas, Sagari R.; Pimbert, Michel P. (The Journal of Peasant Studies, 2024)
The Andhra Pradesh Zero Budget Natural Farming project was implemented by India's State of Andhra Pradesh in 2016 and renamed AP Community Managed Natural Farming (APCNF) in 2020. APCNF is recognised as a sucessful example of peasant-led agroecology by social movements, multilateral UN bodies, governments, and researchers. We offer more critical perspectives here, and argue that this agroecology model deepens inequality and dispossession. Despite claims to the contrary, APCNF is locked in an unchanged productivist paradigm controlled by capital in collaboration with the state. By co-opting agroecology, APCNF closes down options for a just transformation of the dominant agri-food regime.
Keywords: Agroecology; APCNF; Cooption; Greenwashing; ZBNF; Inequality